The Sukulu complex, Eastern Uganda and The origin of the African carbonatites - Williams, Cyril Edward Foxcroft (Department of Geological Sciences, 2016)
The thesis presented is a compilation of both published and unpublished work carried out during the past ten years. The arguments and conclusions are based largely on field observations together with a study of the chemical composition of the rocks involved. Part I of the paper deals with the structure, petrography and economic geology of the Sukulu Complex. Structural Geology: The mapping of the Sukulu-Tororo complex provided the first detailed examination of the structure of an African carbonatite. The most important result of this survey was the demonstration that the carbonatites were emplaced in a plastic condition, in the form of "collars", dykes and ring-dykes, into and around an earlier calcitic plug which occupied the conduit. This concept is diametrically opposed to that previously accepted. (Strauss & Truter, Spitskop. von Eckermann, Alno Island). Later work in other areas (Chilwa Island, Ondurakarume, Homa Mountain) has confirmed the author's interpretation. The regional and surface structure connected with alkaline complexes is discussed and the definite genetic relationship of carbonatites with Elgon type volcanoes is stressed. Petrography: Owing to the deep weathering of the complex at Sukulu the associated alkaline rocks are poorly exposed but the examination of borehole cores shows that the rock types found in many other African carbonatites are also present here. Economic Geology: The economic soil deposit discovered by the author in 1949 is described. This deposit consists of an easily worked, deep eluvial soil containing the tour economic minerals apatite, magnetite, pyrochlore and baddeleyite. The soil covers the perimeter of the carbonatite and tills the wide valley embayments running into the centre of the complex. The description given constitutes the first detailed discussion of the economic geology of a new type of deposit. A brief classification of economic mineral deposits associated with the carbonatite complexes is included. PART II. The Origin of the African Carbonatites. A review is given of the rock types and structures found in alkaline ring complexes and volcanoes of Elgon type. The formation of undersaturated magma is attributed to the segregation of pyroxenes and to some extent plagioclase from a parent basaltic magma. Nephelinite is the type most commonly produced and constitutes the main lava flows of these volcanoes. The development of rocks containing melilite, melanite and primary calcite from nephelinitic magma is shown to be the result of the relative increase in lime, together with desilication of the residual liquid during the crystallisation and segregation of nepheline. Chemical variation diagrams are presented in support of these contentions. Chemical and arithmetical evidence is given to show that the removal of beforsitic carbonatite from nephelinitic magma leaves a phonolitic residual liquid, while the removal of iron-rich, alvikitic carbonatite leaves a trachytic residuum. The mechanism of carbonatite formation is thought to be the exsolution and upward migration of bubbles of carbondioxide during paroxysmal eruptions, the ascending gas chilling the magma and reacting with the dissolved oxides of calcium, magnesium, iron, manganese, barium and strontium to form carbonates. The rising gas streams serve to concentrate the carbonates by agitation and flotation with the establishment of a specific gravity gradient. Revival of pressure from below caused the typical intrusion pattern observed. The hypothesis presented reconciles all the recorded field and chemical data on African carbonatites. Should the hypothesis gain general acceptance, it would be possible to reduce greatly the unwieldy nomenclature in this branch of petrography. It is of interest to note that confirmatory laboratory evidence has recently appeared (O. Tuttle, "Nature", March, 1959) which demonstrates the feasibility of the existence of magmatic carbonates as a separate phase.